Dynamics of damage spreading in the two-dimensional Ising magnet at criticality - Montani, Fernando Fabián (1995)
The spreading dynamics of an initially small damage is studied for the two-dimensional Ising model at criticality using the Glauber dynamics. The number of damaged sites, Nd(t), the survival probability of the damage, P(t), and the mean square distance over which the damage spreads, R²(t), obey a simple power law behavior with critical exponents η⋍ 1.11 ± 0.03 δ ⋍ 0.58 ± 0.03 and z* ⋍ 1.19 ± 0.03, respectively. It is found that the scaling relation df = 2η/z* gives the fractal dimension of the Ising droplets.